Molecular characterization of Listeria spp. isolated from cattle farms, abattoirs, and beef products in Mpumalanga and North-West Provinces, South Africa - Adesiyun, Abiodun Adewale (University of Pretoria, 2024)
Thesis (PhD (Production Animal Studies))--University of Pretoria, 2024.